(untitled) - Hutsko, Joe (Hoboken, N.J., 2015)
iPhone All-in-One For Dummies covers all the basics and beyond to give you hands-on, all-encompassing coverage of your new smartphone. Written in plain English and packed with tons of full-color photographs that help bring the information to life, this friendly guide shows you how to activate the iPhone, control the multi-touch and voice-recognition interfaces, tour the iPhone's built-in apps and settings, set up security features, start sending texts, and configure e-mail. Next, it moves on to tackling the iPhone's more advanced features, like capturing and sharing photos, tapping into maps, acquiring and listening to music, creating and sharing notes and memos, making video calls with FaceTime, and much more.
Keywords: iPhone (Smartphone),Mobile computing,Application software,iPhone (điện thoại thông minh),Điện thoại di động,Phần mềm ứng dụng